The Scientific Women in the Current Spain. Social representations. - García Nieto, María Teresa; Viñarás Abad, Mónica (Historia y Comunicación Social, 2014)
This study is a part of the Project of Investigation for the Promotion of the Gender Equality in the Scientific information (IFIGIC), financed by the Institute of Women, of the Ministry of Health, Social Services and Equality. We here try to highlight the lack of recognition of the scientific women in the actual society in Spain, revealing, in addition, the different images and social representations that the women and the men have towards this group. With this aim in mind, we have performed a study, qualitatively and exploratory, developing three focus groups; one of them formed exclusively by women, other one being constituted by men only, and a mixed third group formed by women and men. The results of the study cannot be more enlightening. The social knowledge, about the persons working scientific investigation in Spain, is very scanty and slightly significant. Women and men do not discern the scientific character of the women and perceive them, simply, as other professional women. Furthermore, women and men have different images from the professional women and these representations correspond, in a peculiar form, to stereotyped schemes. This serious lack of public recognition of the Spanish scientific women and their stereotyped social representation are favoring certain pernicious and not wished effects: the social immobility and the permanency of an unbalanced and unequal situation, manifestly advantageous for men. The project IFIGIC has the intention of changing this unwanted reality, enhancing the promotion of the gender equality in the scientific information, and facilitating, in a progressive way, the process of evolution towards the gender equality in the scientific Spanish scene.
Keywords: women scientific; social representation; stereotypes; media; gender.